Low Compliance to Handwashing Program and High Nosocomial Infection in a Brazilian Hospital - Lizandra Ferreira de Almeida e Borges; Lilian Alves Rocha; Maria José Nunes; Paulo Pinto Gontijo Filho (Interdisciplinary Perspectives on Infectious Diseases)
Background. It is a fact that hand hygiene prevents nosocomial infection, but compliance with recommended instructions is commonly poor. The purpose of this study was to implement a hand hygiene program for increase compliance with hand hygiene and its relationship with nosocomial infection (NI) and MRSA infection/colonization rates. Methods. Compliance to hand hygiene was evaluated in a hospital by direct observation and measured of health care-associated infections, including methicillin resistant Staphylococcus aureus, before and after an educational intervention, using visual poster, colorful stamps, and feedback of the results. Results. Overall compliance did not increase during intervention, only handwashing before and after patient contact has improved from 40% to 76% (𝑃=0.01) for HCWs, but NI and MRSA rates remained high and stable. Conclusion. In a combination of high prevalence of NI and low compliance to hand hygiene, the programme of measure does not motivate the HCW hand hygiene. Future interventions should employ incremental evaluation to develop effective hand hygiene initiatives.